Pengaruh Gaya Belajar Dan Cara Mengajar Terhadap Hasil Belajar Siswa - Adelia Salsabila; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the influence of learning styles and how to teach on student learning outcomes. The population used in this study was students of SMK Negeri 48 Jakarta. The number of samples used was 108 respondents. The method of data collection is questionnaire. The data analysis techniques used SmartPLS (Partial Least Square) Statistics. The results of this study show: 1) Learning styles have positive values and have a significant effect on learning outcomes, 2) How to teach have a positive effect and have a significant effect on learning outcomes, 3) Learning styles and how to teach have a positive and significant effect on learning outcomes.